Oily wastewater treatment using membrane cascade systems - Peng, Hui (University of Ottawa (Canada), 2008)
Ships produce a large amount of oily wastewaters such as bilge water which needs to be treated prior to being discharged. Bilge water is a very challenging wastewater to treat due to large variations in production rates and the complex nature of the wastes in solution. Ever increasing regulations are being imposed on the treatment and release of bilge water to the environment. The objective of this study was to develop a membrane process to remove oil and grease from bilge water to a level where it could be discharged into sensitive environments. This work focused on five elements of study: (1) Evaluation of feasibility and performance of bilge water treatment using a pilot scale microfiltration/ultrafiltration (MF/UF) hybrid membrane system; (2) Development of a pilot scale membrane cascade for selective removal of oil to 0 ppm or a non-detectable level from bilge water while minimizing concentrate production; (3) Establishment of an analytical method to extract and analyze organic species at very low concentration levels for the analysis of oil and grease content found in bilge water and membrane permeate; (4) Investigation of environmentally friendly membrane cleaning methods; and (5) Study of filtration mechanism in the treatment of bilge water using ultrafiltration and microfiltration. Pilot scale membrane cascade systems were designed and tested for the treatment of synthetic bilge water. Experimental results showed that the pretreatment of this oily wastewater using microfiltration, prior to ultrafiltration, is desirable as used oils and particulates can block the feed channels of UF spiral and hollow fiber modules. Backflushing is an effective technique to reduce fouling caused by "sticky" cakes in synthetic bilge water treatment using a microfiltration membrane. Membrane support structure was found to be critical in enhancing flux during backflushing. This work outlined the need for microfiltration membranes offering good particulate clearance to be used in backflushing coalescence applications. A pilot scale membrane hybrid system, consisting of a coalescing backflushed microfiltration membrane used as a pretreatment and an ultrafiltration membrane as a final polishing step, was found to be very effective in this application, producing permeate with oil and grease content well below the allowable discharge limit (15 ppm) for coastal waters. Another membrane cascade system using tubular MF and UF membranes in a first stage and flat sheet UF membranes in a second stage was found to be able to produce water containing below detectable levels of hexane extractable material. Permeates of various molecular weight cut-off (MWCO) membranes from the cascade system were collected and analyzed using an extraction procedure followed by gas chromatography (GC). Analytical results showed that solid phase extraction using ENVI-18 sorbent retained much of the organic matter found in the bilge water and could not preserve the molecular weight distribution in the oil mixture used to prepare synthetic bilge water. n-Hexane liquid-liquid extraction technique was found to be able to preserve the molecular weight distribution of diesel and lubricating oils separated by ultrafiltration. The effect of membrane MWCO in separation of oil and grease was also studied in this work. Environmentally friendly physical membrane cleaning methods, such as backflushing with hot water or steam followed by pressurized air, were found effective in regenerating membrane flux for large pore KOCH carbon membranes in the treatment of synthetic bilge water using a MF/UF hybrid system. The beneficial effects for steam cleaning were found to be evident. Optimal cycle times between physical cleanings were determined. Filtration mechanisms in the treatment of synthetic bilge water were studied using four classical filtration models and a combined model. Experimental results of the research conducted in this study suggested that it is possible to achieve the target of removing oil from bilge water to 0 ppm or non-detectable levels through the proper design of the membrane system, selection of appropriate membranes, determination of optimal operating parameters, and assessment of membrane performance.
Keywords: Engineering, Chemical.; Engineering, Marine and Ocean.; Engineering, Environmental.